Androgens inhibit androgen receptor promoter activation in motor neurons - Guglielmo Vismara (Neurobiology of Disease, 2009)
The androgen receptor (AR), a ligand-activated transcription factor, has been found mutated in several human diseases. While some mutations reduce, others potentiate AR functions generating different endocrine dysfunctions. A peculiar AR mutation, the CAG-repeat expansion encoding the AR-polyglutamine (polyQ) tract, generates a neurotoxic gain-of-function(s) in this mutant AR (ARpolyQ). This leads to the motor neuronal disease Spinal and Bulbar Muscular Atrophy (SBMA), in which the transcriptional AR down-regulation might have beneficial impacts. We thus analysed the AR-promoter/5′-UTR activation and androgenic regulation, demonstrating that its constitutive activity is considerably high in motor neurons (NSC34). Testosterone, dihydrotestosterone (DHT), but not estradiol, inhibited AR promoter activation. Thus AR establishes a negative control on its own functions, in opposition to that described on classical androgen-responsive elements (ARE) of the AR gene. The AR/DNA interaction is required for this action, since DHT does not inhibit AR expression in presence of an AR (AR_ΔPhe581) lacking DNA binding activity. The minimal inhibitory region spans from −740/+570 bp, where “in silico” analysis showed a putative AR binding site; deletion studies excluded that this ARE may be involved in this inhibition. A similar effect of DHT has also been observed in AR negative prostate cancer DU145 cell line transfected with the AR. Moreover, androgens down-regulate the expression of the endogenous AR gene in an AR positive prostate cancer LNCaP cell line. Interestingly, in immortalized motor neurons, ARpolyQ was much less effective than wtAR on the positive androgenic control on classical AREs, while ARpolyQ and wtAR had similar inhibitory properties on the AR promoter/5′-UTR activation. This strongly suggests that, in motor neurons, the two types of AR gene androgenic regulation involve different mechanisms. Thus, by acting on the AR promoter it would be possible to reduce AR levels in motor neurons, providing novel approaches to treat SBMA.